Estratégias de enfrentamento de mães na convivência com filhos desnutridos - Magalhães, Maria de Lourdes Benevides de (2012)
Malnutrition should be understood as a multi-dimensional expression characterizing a series of extremely unfavorable situations and living conditions that act upon an individual. To understand the perceptions of mothers of malnourished children regarding the realities of their lives, starting with a context of social disadvantage and at the same time analyzing theircoping strategies in the face of their precarious living conditions. In addition, their impressions of the institution where their children are cared for were also recorded. The study was conducted with seven women, mothers of malnourished children cared for at the Institute for the Promotion of Nutrition and Human Development - IPREDE, located in Fortaleza, Ceará, between May and October 2011. A qualitative methodology was adopted, developing ethnographic accounts, and the theoretical framework was grounded in the interdisciplinary field of Public Health. A triangulated discussion was carried out using systematic and participatory observation of semi-structured individual interviews, document research and interpretation by the researcher, with the aid of a field diary and constant reference to the specialized literature. The empirical material obtained was analyzed using the technique of discourse analysis. The researcher monitored the lives of these women in their place of residence, visits to health care centers and IPREDE. The results reveal a strong link between child malnutrition and difficulties in the construction of motherhood and bonding between mother and child. The women, marked by fragility and guilt remain limited, fixed on concerns about motherhood; unable to see a way out or opportunities to live better. Faced with so many hardships, the subjects try to seek strategies to deal with adversity, in both the cognitive and the emotional sense, trying to cope with the stressful situations present in their day-to-day. They look for support from their family, friends or neighbors. They work, watch soap operas, walk, sleep, pray, seek a supportive institution, think positively, change partner, get involved with a lover and seek justice. At IPREDE, the mothers place particular importance on having a space for exchanges and more democratic relationships with professionals, where they can express themselves and share their "heartaches." Their confidence in biomedical knowledge when seeking guidance and understanding about their children’s health was also observed.These spaces appear to have contributed to their personal growth; strengthening their chances of coping. It is concluded that nutritional intervention programs can obtain better results when the life story of the mothers is valued as a supporting factor in the process of determining and recovering from malnutrition. Understanding how a woman lives with her child in their natural environment may provide insights on a case by case basis. The planning of pleasant activities and audio-visual resources can promote more relaxed and participatory learning situations. It is also suggested that the mother’s opinions and preferences be consulted, as this may stimulate their inclusion and self-affirmation as active subjects in their child’s care and healing. Deeper and more individualized psycho-emotional care and attention to the dyad,may favor the strengthening of the mother-child bond.